Reputation and emotion: How the mind drives our food preferences and choices. (October 2022) - Cancellieri, Uberta Ganucci; Petruccelli, Irene; Cicero, Lavinia; Milani, Alessandro; Bonaiuto, Flavia; Bonaiuto, Marino
Highlights: Food with a higher reputation are those with a higher willingness to eat. Food with a higher reputation evoke less negative emotions and more positive ones. Positive and negative food emotions influence the willingness to eat that food. Cognitive factors influence the "willingness to eat" more than emotional factors. The willingness to eat food with a worse reputation is more influenced by emotions. Abstract: The research aims to investigate how the reputation of foods and the emotions elicited by it predict the willingness to eat certain foods. Specifically, the study analyzed a regression model that investigates the impact of "food reputation" on "willingness to eat" through the sequential mediation of "food emotions" (positive and negative) and "food preference" in both participants' preferred food (pizza) and their dispreferred food (offal). Analysis revealed that "food reputation" generally has a positive and significant indirect effect (through the mediation of "food emotions" and "food preference") on the "willingness to eat" both preferred and dispreferred food. It also emerged a positive mediation effect of "positive food emotions" in predicting the "willingness to eat" both preferred and dispreferred food. Regarding "negative food emotions" these have a negative mediation effect in predicting "willingness to eat" the dispreferred food. Results finally showed that both positive and negative food emotions have a greater impact on the "willingness to eat" the dispreferred food than the preferred one. The results highlight how emotions related to a particular food significantly influence the willingness to eat it. However, a clear predominance of cognitive factors (food reputation) over emotional factors in predicting the "willingness to eat" of both preferred and dispreferred foods was also found. This predominance is also confirmed by the latest hypothesis, which shows that foods with a worse reputation are also those that are more influenced by elicited emotions (both positive and negative).